Hip protectors: recommendations for biomechanical testing—an international consensus statement (part I) - Robinovitch, S. N.; Evans, S. L.; Minns, J.; Laing, A. C.; Kannus, P.; Cripton, P. A.; Derler, S.; Birge, S. J.; Plant, D.; Cameron, I. D.; Kiel, D. P.; Howland, J.; et al. (Osteoporosis international, 2009)
Introduction Hip protectors represent a promising strategy for preventing fall-related hip fractures. However, clinical trials have yielded conflicting results due, in part, to lack of agreement on techniques for measuring and optimizing the biomechanical performance of hip protectors as a prerequisite to clinical trials. Methods In November 2007, the International Hip Protector Research Group met in Copenhagen to address barriers to the clinical effectiveness of hip protectors. This paper represents an evidence-based consensus statement from the group on recommended methods for evaluating the biomechanical performance of hip protectors. Results and conclusions The primary outcome of testing should be the percent reduction (compared with the unpadded condition) in peak value of the axial compressive force applied to the femoral neck during a simulated fall on the greater trochanter. To provide reasonable results, the test system should accurately simulate the pelvic anatomy, and the impact velocity (3.4 m/s), pelvic stiffness (acceptable range: 39-55 kN/m), and effective mass of the body (acceptable range: 22-33 kg) during impact. Given the current lack of clear evidence regarding the clinical efficacy of specific hip protectors, the primary value of biomechanical testing at present is to compare the protective value of different products, as opposed to rejecting or accepting specific devices for market use.